A Preview of Total Quality Management (TQM) in Public Services - Enggartyasti, Avia; Caraka, Rezzy Eko (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.09.TAHUN 2017, 2017)
Total Management System or Total Quality Management (TQM)  is a management system that focuses on the Customer by involving all levels of employees in upgrading or continuous improvement. Total Quality Management used data and effective communication to integrate his discipline into the culture and quality of company activities. In short, Total Quality Management (TQM) is a management approach to achieve long-term success through customer satisfaction. This study had two objectives. The first objective was to examine challenges when implementing TQM in public organisations. The second objective was to argues that TQM brings good implications to public services to enhance service quality.
Keywords: Business, TQM, Quality, Management, Business, Customer